Impact of genotype and growing season on productive traits of spring two-row barley - Bratković Kamenko; Đorović Sofija; Luković Kristina; Perišić Vladimir; Rakonjac Aleksandra; Matković Stojšin Mirela (Selekcija i Semenarstvo, 2025)
Barley (Hordeum vulgare L.) is one of the most important cereals in the world, and in Serbia it ranks third in terms of cultivated area, after corn and wheat. However, the production of spring barley faces challenges caused by climate change, which have a negative impact on grain yield and grain quality. Therefore, the aim of this research was to examine the influence of genotype, growing season and their interactions on the productive traits of spring two-row barley. The research was conducted in Kragujevac during 2022 and 2023 growing seasons, where the experiment was set up using the method of random assignment in four replications. As plant material, three two-row spring barley genotypes were used: Jadran, Scarlett and L-1/6-95. The results of the research show that the factor of growing season had a dominant effect in the expression of the number of grains per spike, number of grains per m², thousand grain weight, and grain yield, with the largest share in the variation of the number of grains per m² (77% of the treatment sum of squares), while it did not significantly affect the expression of grain weight per spike, which was mostly influenced by the genotype (62.5% of the treatment sum of squares). In the second season (2023), which was characterized by lower temperatures and evenly distributed rainfall, higher values of number of grains per spike (by 12.95%), number of grains per m² (by 55, 21%), grain weight per spike (by 11.82%), and grain yield (by 46.36%) compared to the first season (2022). However, the higher amount of precipitation during the grain filling phase in 2023 season had a negative impact on the thousand grain weight, which was 5.96% less compared to 2022. These results indicate that excessive rainfall at the grain filling stage can negatively affect grain quality. Also, the factor of genotype had a significant influence on the variation of all traits, except for the number of grains per spike. Genotype Scarlett stood out as the most productive, with the highest average values of number of grains per spike (24.4), number of grains per m² (7821), thousand grain weight (47.3 g), grain weight per spike (1.25 g), and grain yield (3.64 t ha-1). On the other hand, genotype L-1/6-95 had slightly lower values of all these traits, while genotype Jadran had the lowest values in all parameters (except thousand grain weight). These results confirm that genotypes have a significant impact on productive traits, where the genotype Scarlett proved to be the most suitable for production in our agroecological conditions. The high correlation coefficient between grain yield and the number of grains per m² (0.988) confirms that the number of grains per m² is a key trait for achieving a high grain yield of two-row spring barley. On the other hand, a highly significant negative correlation was obtained between the number of grains per m² and the thousand grain weight (-0.500), which is the result of the influence of excessive rainfall in June on grain filling, which did not negatively affect the number of grains. Nevertheless, a high value of the thousand grain weight was found in all genotypes, which makes them suitable for use in the brewing industry. Knowing the influence of genotype and the growing season and their interactions emphasizes the need to adapt agrotechnical practices, to choose appropriate genotypes to achieve high yield and high grain quality.